The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/ijd.12455
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for skin diseases among antiretroviral‐naïve HIV‐infected pregnant women in Dar es Salaam, Tanzania

Abstract: Background Reduced cell-mediated immunity associated with pregnancy may cause a flaring or exacerbation of some skin conditions. Little is known about the magnitude of and risk factors for skin diseases among human immunodeficiency virus (HIV)-infected antiretroviral therapy-naïve pregnant women. Methods Cross-sectional study of 1078 HIV-infected antiretroviral therapy-naïve pregnant women was conducted in Dar es Salaam, Tanzania. Skin diagnoses were mainly clinical. Log-binomial regression models were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…This unacceptable and constant high rate of AHD among pregnant women has important clinical and public health implications, including the strengthening of ongoing HIV-control efforts specially focused in women of childbearing age. The proportion of women with AHD in this cohort was lower than the 37% estimated in the general population in Mozambique, although this figure is from 2014 [ 8 ], and similar to reports in pregnant women from neighboring South Africa (12%) and Tanzania (12-14%) [ 13 , 38 , 39 ]. The results of this study showed that a high proportion (76.2%) of pregnant women with AHD had been on ART for a long period (nearly 2 years), suggesting suboptimal case management regarding detection of low adherence and/or treatment failure before the current pregnancy.…”
Section: Discussionsupporting
confidence: 78%
“…This unacceptable and constant high rate of AHD among pregnant women has important clinical and public health implications, including the strengthening of ongoing HIV-control efforts specially focused in women of childbearing age. The proportion of women with AHD in this cohort was lower than the 37% estimated in the general population in Mozambique, although this figure is from 2014 [ 8 ], and similar to reports in pregnant women from neighboring South Africa (12%) and Tanzania (12-14%) [ 13 , 38 , 39 ]. The results of this study showed that a high proportion (76.2%) of pregnant women with AHD had been on ART for a long period (nearly 2 years), suggesting suboptimal case management regarding detection of low adherence and/or treatment failure before the current pregnancy.…”
Section: Discussionsupporting
confidence: 78%